Synthesis of Hydroxyapatite Nanoparticles from Egg Shells by Sol-Gel Method: An Analytical Approach - Azis , Y.; Adrian, M.; Alfarisi, C. D.; Khairat, .; Sri, R. M. (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
Hydroxyapatite, [Ca10(PO4)6(OH)2, (HAp)], is a mineral that is widely used in medical field, particularly as a bone and tooth substitute. Using the sol-gel method, hydroxyapatite nanoparticles were successfully synthesised from egg shells as a calcium source in this work. The egg shells were calcined, hydrated (slaking), and carbonated to produce Precipitated Calcium Carbonate (PCC). PCC is a calcium carbonate compound (CaCO3) that can be processed from the material through a series of chemical reactions. PCC particles’ is homogeneous that in the same size with micro-scale particle. Then the PCC was added (NH4)2HPO4 to form HAp with variation the mole ratio Ca and P (1.57; 1.67 and 1.77), aging time (24, 48, and 72 hr) and under basic condition pH (9, 10 and 11). XRD, FTIR, and SEM-EDX were used to characterise the formation of hydroxyapatite biomaterial. The XRD patterns revealed that the products were crystals of hydroxyapatite. The best results were obtained after 24 hours of ageing at pH 9 with a hexagonal hydroxyapatite structure. The particle size of HAp was 35-54 nm, and the morphology of hydroxyapatite observed using SEM revealed that the crystal of hydroxyapatite was uniform.